Efeito da prática musical no processamento auditivo em escolares de sete a 14 anos de idade - Cioqueta, Elenara Pilar (2006)
It is known that the understanding of the speech is essential for a normal communication and it is dependent of the hearing abilities. Such abilities, among others, are fundamental for the understanding of the acoustic information, they depend on the perceptive ability of the sounds and each person's individual capacity. The capacity of acoustic interpretation can be perfected by the hearing training through the music. In general, the music plays an important part in the education, because it is through it that trains the perception and the discrimination of the most varied sounds (Benenzon,1985). The objective of this research is to compare the results of the evaluation of the hearing processing of two groups of scholars, one with musical experience and other inexperienced, both formed by 15 scholars. All of them were submitted to the anamnesis, visual inspection of the external acoustic meato, evaluation basic audiology (tonal audiometry preliminary-ATL, Threshold of Recognition of Speech-LRF, Percentile Index of Recognition of Speech-IPRF and Measures of Imitância Acoustics-MIA) and evaluation of the hearing processing (Staggered Spondaic Words-SSW, speech in the noise, Pitch Pattern Sequence-PPS and Duration Pattern Sequence-DPS). The results of the evaluation of the hearing processing were submitted to the statistical analysis through the no-parametric Test of Kruskal-Wallis. The rejection level for the nullity hypothesis was set in a smaller value or same to 5% (p <0,05). The following results were obtained: in relation to the tests SSW and speech in the noise, ECEM s group presented superior values, however no statistical significant, when analyzed the appraised ears. In relation to the DPS test, the same happened, however the form of the scholars answer was included (murmuring or nomination). For the PPS test, ECEM s group presented better results and statistical significant, so much for analysis of the appraised ears, as for the form of the scholars answer. Still, as results, it was observed in all the applied tests, that the answers of the group of ECEM were better and more clear, and the qualitative results differed significantly of the results ESEM s group. We concluded that the results of the evaluation of the hearing processing of the group of ECEM were superior to the results of the group of ESEM.